Susceptibilidad de Delia platura a siete aislamientos de nematodos entomopatógenos de la zona Central Andina de Colombia - Jaramillo Contreras, Carolina Maria; Pontificia Universidad Javeriana (2013)
The seed maggot, Delia platura, is a major pest of spinach crops in the savanna of Bogotá. In Colombia, chemical insecticides are used to manage the pest; however, because its management is not integrated,information about pest management in spinach is still undetermined. Here, we evaluated the susceptibility of D. platura to seven species of entomopathogenic nematodes from the central Andean region ofColombia. Additionally, under laboratory conditions, we produced and evaluated different doses of infective juveniles (IJs) of the most virulent species. In the laboratory, we used yellow potatoes (Solanum phureja) for breeding to obtain third instar larvae; we then exposed them to infective IJs 2500/species. Once we selected the most virulent species, we exposed D. platura to 500, 1000, 2000, 4000 and 8000 IJs/larvae. We obtained the best results with Steinernema sp.3 with mortality of 75-88% at doses of 4000-8000 IJs, and found that LD50 is 1314 JIs/larvae and LD95 is 15259 JIs/larva. We also evidenced the successful reproduction of Steinernema sp.3 in D. platura, with a mean production of 670±7.67 JIs/larvae for eighteen days. Thus, the seed fly is highly susceptible to Steinernema sp.3 making this species a potential controlling agent for this pest.